Bifidobacterium longum CCM 7952 Promotes Epithelial Barrier Function and Prevents Acute DSS-Induced Colitis in Strictly Strain-Specific Manner - Srutkova, Dagmar; Schwarzer, Martin; Hudcovic, Tomas; Zakostelska, Zuzana; Drab, Vladimir; Spanova, Alena; Rittich, Bohuslav; Kozakova, Hana; Schabussova, Irma (PLOS ONE, 2015)
Background Reduced microbial diversity has been associated with inflammatory bowel disease (IBD) and probiotic bacteria have been proposed for its prevention and/or treatment. Nevertheless, comparative studies of strains of the same subspecies for specific health benefits are scarce. Here we compared two Bifidobacterium longum ssp. longum strains for their capacity to prevent experimental colitis. Methods Immunomodulatory properties of nine probiotic bifidobacteria were assessed by stimulation of murine splenocytes. The immune responses to B. longum ssp. longum CCM 7952 (Bl 7952) and CCDM 372 (Bl 372) were further characterized by stimulation of bone marrow-derived dendritic cell, HEK293/TLR2 or HEK293/NOD2 cells. A mouse model of dextran sulphate sodium (DSS)-induced colitis was used to compare their beneficial effects in vivo. Results The nine bifidobacteria exhibited strain-specific abilities to induce cytokine production. Bl 372 induced higher levels of both pro- and anti-inflammatory cytokines in spleen and dendritic cell cultures compared to Bl 7952. Both strains engaged TLR2 and contain ligands for NOD2. In a mouse model of DSS-induced colitis, Bl 7952, but not Bl 372, reduced clinical symptoms and preserved expression of tight junction proteins. Importantly, Bl 7952 improved intestinal barrier function as demonstrated by reduced FITC-dextran levels in serum. Conclusions We have shown that Bl 7952, but not Bl 372, protected mice from the development of experimental colitis. Our data suggest that although some immunomodulatory properties might be widespread among the genus Bifidobacterium, others may be rare and characteristic only for a specific strain. Therefore, careful selection might be crucial in providing beneficial outcome in clinical trials with probiotics in IBD.